Potent Tetrahydroquinolone Eliminates Apicomplexan Parasites - McPhillie, Martin J.; Zhou, Ying; Hickman, Mark R.; Gordon, James A.; Weber, Christopher R.; Li, Qigui; Lee, Patty J.; Amporndanai, Kangsa; Johnson, Rachel M.; Darby, Heather; Woods, Stuart; Li, Zhu-hong; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Apicomplexan infections cause substantial morbidity and mortality, worldwide. New, improved therapies are needed. Herein, we create a next generation anti-apicomplexan lead compound, JAG21, a tetrahydroquinolone, with increased sp3-character to improve parasite selectivity. Relative to other cytochromeb inhibitors, JAG21 has improved solubility and ADMET properties, without need for pro-drug. JAG21 significantly reduces Toxoplasma gondii tachyzoites and encysted bradyzoites in vitro, and in primary and established chronic infections in vivo. Moreover, JAG21 treatment leads to 100% survival. Further, JAG21 is efficacious against drug-resistant Plasmodium falciparum in vitro. Causal prophylaxis and radical cure are achieved after P. berghei sporozoite infection with oral administration of a single dose (2.5mg/kg) or three days treatment at reduced dose (0.625mg/kg/day), eliminating parasitemia and leading to 100% survival. Enzymatic, binding, and co-crystallography/pharmacophore studies demonstrate selectivity for apicomplexan relative to mammalian enzymes. JAG21 has significant promise as a pre-clinical candidate for prevention, treatment and cure of toxoplasmosis and malaria.